Case report: Delusional infestation in dementia with Lewy bodies - Taomoto, Daiki; Kanemoto, Hideki; Satake, Yuto; Yoshiyama, Kenji; Iwase, Masao; Hashimoto, Mamoru; Ikeda, Manabu (Frontiers in Psychiatry, 2022)
Background: Delusional infestation is characterized by delusions of being infested with parasites, vermin, or small insects and is frequently accompanied by tactile and visual hallucinations. Herein, we report two cases of dementia with Lewy bodies (DLB) with delusional infestation. Case presentation Case 1 was an 83-year-old man. At the age of 75, he began to show symptoms of rapid eye movement sleep behavior disorder. At the age of 83, he began to complain of visual hallucinations of people and delusional infestation with tactile and visual hallucinations of insects, resulting in the use of insecticides for non-existent insects. He also complained of mild amnesia and was admitted to our psychiatric ward for evaluation and treatment. After admission, the delusional infestation disappeared without any new medication. Based on our examinations, he was diagnosed with probable DLB with delusional infestation. He was treated with 5 mg/day of donepezil hydrochloride; his visual and tactile hallucinations disappeared, and the delusional infestation never recurred. Case 2 was a 69-year-old woman. At the age of 60, she underwent clipping for subarachnoid hemorrhage. At the age of 65, she began to have visual hallucinations of people. At the age of 67, she began to complain of visual illusions in which she mistook lint for insects. At the age of 69, she developed delusional infestation and mild amnesia. She took various actions to get rid of these non-existent insects, including insecticide use, consulting an exterminator, and visiting several dermatologists. She eventually burnt her leg in an attempt to kill the non-existent insects. Based on our examinations, she was diagnosed with prodromal DLB in addition to subarachnoid hemorrhage sequelae. We determined that her delusional infestation was caused by DLB rather than subarachnoid hemorrhage sequelae based on the course of her symptoms. She was treated with a combination of 3 mg/day of donepezil hydrochloride and 12.5 mg/day of quetiapine. Thereafter, the delusional infestation partially improved, and she took no further action against non-existent insects. Conclusions: Delusional infestation may be caused by DLB. Acetylcholinesterase inhibitors may be effective for delusional infestation in DLB, although antipsychotics may also be needed in severe cases.